Development stimulation with finger painting techniques and toddler age tantrum frequency - Tri Maryani; Dwiana Estiwidani (Jurnal Kesehatan Ibu dan Anak, 2020)
Temper tantrums are destructive behavior in the form of overflows that can be physical (hitting, biting, pushing) or verbal (crying, screaming, whining) or constantly sulking because the child has not been able to express emotions. Through finger painting will help children express their emotions through color games. The purpose of this study was to analyze the effect of growth stimulation with Finger Painting techniques on motor development and tantrum frequency of toddler-age children. Quasi-experimental research method with pretest-posttest with control group design. This research was conducted in Posyandu at Mantrijeron, Yogyakarta City from July to August 2018. The population in this study were all toddlers aged 1-3 years old. Subjects were selected using the purposive sampling technique as many as 82 respondents. The results show that there was a difference of occurrent temper tantrums before (average in treatment group=48.8; average in control group=45.8) and after treatment (average in treatment group=31.3; average in control group=36.7). The independent t-test analysis showed that there was an effect of stimulation with finger painting technique on the tantrum frequency of toddlers (p-value 0.0001). There was an influence of developmental stimulation with finger painting techniques on the frequency of toddler tantrums.